Analisis Performa Boiler Berbahan Bakar Kombinasi Fiber Dan Cangkang Pada Boiler Takuma N-600 SA - Eli Simanjuntak; Muhammad Idris; Jufrizal Jufrizal (CV. IRA PUBLISHING, 2023)
A boiler Is a steam-producing closed vessel that can convert chemical energy from fuel into pressurized steam. The steam is used as an electrical power source and for the processing of oil palm fruit. Researchers use direct observation methods to identify specimens and parameters. To analyze the efficiency of thermal boilers and Specific Fuel Consumption (SFC) using 100% fiber fuel and a combination of 70% fiber and 30% shell. From the results of this study, it is stated that using 100% fiber fuel produces 68.1% thermal boiler efficiency, and an SFC value of 13.37 kg/kWh is obtained. The combined fuel use of 70% fiber and 30% shell results in 74.2% thermal boiler efficiency and an SFC value of 10,98 kg/kWh is obtained. So that the efficiency of thermal boilers has increased by 6.1% and the SFC value has decreased by 2.39 kg/kWh. The improvement in boiler performance and low SFC value is due to the high calorific value of fiber and shell combination fuel which is 12799.343 kJ/kg and low fuel consumption of 5492.53 kg/hour.